Dilematis Antara Kesulitan Siswa Dengan Guru Dalam Pembelajaran Daring Pada Masa Pandemic Covid-19: Sebuah Upaya Aksidental MTs. Muhammadiyah Wuring - Mohammad Fitri; Murniati Murniati; Gis la Nuwa (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
The purpose of this study was to determine students' difficulties in online learning and to determine the efforts of teachers in overcoming student difficulties in online learning during the Covid-19 pandemic. The method used in this research is a descriptive qualitative approach by describing the teacher's efforts in overcoming student difficulties in online learning during the Covid-19 period at MTs. Muhammadiyah Wuring. This study uses data collection techniques, namely observation, interviews, and documentation. The results of this study can be seen from several student difficulties in online learning such as a) absence of 4G networks, b) reduced income c), assignment methods and d) absence of Android phones. The teacher's efforts in overcoming student difficulties in online learning such as a) assignment methods, b) providing motivation, c) providing advice, d) providing online explanations, e) installing Wifi. By knowing the various difficulties of students and the efforts of teachers in overcoming student difficulties in online learning, researchers hope that all of us, especially schools, teachers, parents, and the government to make input in the future.